Environmental Characteristics of Fishermen's Settlements as a Form of Local Wisdom of Coastal Communities in Karangsari Village, Tuban - Bahar, Faisal (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2019)
Settlement is an area that functions as a residence and activity for its inhabitants. The characteristics of a settlement are influenced by the relationship between humans and humans, humans and nature, humans and the Creator.Â  The purpose of this study was to identify the characteristics and factors that influence the formation of the fishermen's settlement of Karangsari Village, Tuban. Settlements are formed not only because of physical strength, but also from social cultural factors and community activities. This study uses a qualitative method with a rationalistic approach. Methods of collecting data by interviewing several local communities and field observations. The results of this study show the characteristics of the settlement environment of Karangsari Tuban fishermen, which is a combination of human mindset and culture that produces an environmental characteristic that is easily recognized through the physical structure of the environment, as well as community activities in the environment.Â DOI: https://doi.org/10.26905/lw.v11i1.2712 Â